Far from shore - Thorpe, Kiki (Thorpe, Kiki. Never girls, 2015)
"The Never Girls have heard about a boy who lives in Never Land--a legendary boy who brings adventure wherever he goes. A boy named Peter Pan. Kate can't wait to meet him. But Tinker Bell knows that Peter is also good at causing trouble. Will this be an adventure, or a disaster?"--